Impact of digital health interventions on pain and symptom management in home hospice patients: A systematic review and meta-analysis protocol - Thiago Oliveira Dos Santos; Fábila Fernanda Dos Passos Da Rosa; Kleyton Santos Medeiros; Francis Solange Vieira Tourinho (PLoS ONE, 2025)
Background The growing global demand for palliative care, particularly in low- and middle-income countries, underscores the urgent need for innovative strategies to ensure symptom control and quality of life for patients with advanced illnesses. Among these strategies, digital health interventions (DHIs) have emerged as promising tools to support pain and symptom management in home hospice settings, especially for cancer patients. Objective This protocol outlines a systematic review and meta-analysis designed to evaluate the effectiveness of digital health interventions in managing pain and other symptoms among cancer patients receiving palliative care at home. Methods This review will include randomized clinical trials and quasi-randomized clinical trials that assess the impact of digital health interventions on pain and symptom control in adult cancer patients under palliative care at home. Studies will be identified through searches in major bibliographic databases, following PRISMA-P guidelines and the Cochrane Handbook. Only peer-reviewed publications will be considered. Interventions must align with the World Health Organization’s definition of DHIs. The primary outcome is the effectiveness of these interventions in pain management compared to traditional in-person care. Expected results This review is expected to identify and synthesize evidence on the effectiveness of DHIs in improving pain and symptom control, as well as overall patient well-being in palliative home care settings, Conclusion The findings will provide a comprehensive understanding of the role of digital technologies in enhancing palliative care delivery, guiding clinical practices and policy decisions aimed at optimizing end-of-life care through remote support. This protocol is registered in the International Prospective Register of Systematic Reviews (PROSPERO): CRD420250572413